Diplomasi Indonesia Di Tengah Persaingan Amerika Serikat dan Cina - Hilda Yunita Wono; M. Masad Masrur; Kirana Ratu Sekar Kedaton; Muh. Rifqy Hasbullah (JURNAL LENSA MUTIARA KOMUNIKASI, 2022)
There are concerns that make attention in reclamation construction in the South China Sea. Apart from that, the divisions in the field of trade, competition in the context of geopolitics and technology that occurred in the two countries, the United States (US) and China, were considered to be the triggers for the arrival of a new Cold War. The background to the conflict between the two is a form of open and strategic competition carried out in order to obtain the label of the best country in the 21st century. US-China relations were originally in the form of a cooperative framework which then shifted into a strategic and open battle. China considers that the US prioritizes resilience over all the advantages it already has, but now it has begun to decline. Meanwhile, the US considers that China is increasingly terrorizing security, making noise over the prosperity of its citizens, hindering people's values and the value of egoism. From the point of view of the Indonesian state, the crisis in US-China relations needs to be managed through the concept of dynamic equilibrium in order to safeguard its national interests. The research uses a descriptive exploratory type of research method (Mas'oed, 1994:68), which will examine the impact of competition between the US and China on Indonesia's diplomacy strategy. This paper analyzes the increasing US-China competition and its impact on Indonesia's diplomatic strategy. The US-China tensions were caused by a struggle between the two over the goal of becoming the number one strongest figure in the world. The US, which has long been known as a super power country, feels its position is being threatened by the new emerging power China. Countries in the ASEAN region, including Indonesia, as a middle power country, should improve their diplomatic strategies and consider their position. The countries in the region are trying to balance and "play" under the affairs of a number of great power countries.